Peran Keteladanan Pemimpin dalam Keluarga Berdasarkan Efesus 5: 21-6:4 - Joko Santoso; Sukirdi Sukirdi (Sekolah Tinggi Theologia Nazarene Indonesia, 2021)
God created a man for a purpose. Humans can achieve goals because God gives knowledge and abilities about these goals. That is how God establishes a leader in the family. God equips one's needs to be able to lead a family properly, appropriately and successfully. Leadership in the family is referred to as the head of the family, usually led by a man. Man in the family stands as husband to wife and as a father to children. A man carries out this leadership goal as leaders in providing the right, correct and good role models. It is not easy for family members to face a pandemic situation that limits all activities in living every day, so it impacts relationships and interactions. It can even lead to disputes and conflicts between family members. Researchers used qualitative methods with an exposition, interview and literature approach. The results and discussion found the basics of exemplary leaders in the family and then applied them in everyday life.